FAKTOR - FAKTOR PENYEBAB STRES AKADEMIK MAHASISWA KEPERAWATAN TAHUN PERTAMA SELAMA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Hutabarat, Nanik Saryati; Elita, Veny; Utomo, Wasisto (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p06, 2022)
Distance learning is the solution for carrying out teaching and learning activities during pandemics and causing first-year students to experience academic stress. This study aims to determine the factors that cause stress in first-year students of the Faculty of Nursing, Riau University, during distance learning in the Covid-19 pandemics. This study used a descriptive correlation research design using a  cross-sectional  approach. The research sample was 134 respondents who were taken based on inclusion criteria using  the total sampling technique.  The analysis used univariate analysis to see the frequency distributions and bivariate using  the chi-square test.  The instrument used is the questionnaire  Depression Anxiety Stress Scale  (DASS) and the  Perceived Stress Scale  (PSS) via  google form  consisting of 28 statements that have been tested for validity with r count 0,599-0,802 > r table (0,444) and r count 0,548-0,740 > r table (0,444). This study showed that the majority of students experienced moderate stress (52,2%). It is indicated that the factors related to student's academic stress are the task and learning load (p = 0,002), classmates (p = 0,003), and the learning environment (p = 0,004). Factors that were not related to student stress levels were knowledge (p = 0,060), parental support (p = 0,785), and lecturer support (p = 0,142). The result of the research level of academic stress in first-year students of the Faculty of Nursing, Riau University is in the moderate category.